On the path toward a universal outflow mechanism in light of NGC 4151 and NGC 1068. Issue Volume 15:Issue S359(2020) (March 2019) - May, D.; Steiner, J. E.; Menezes, R. B.
Abstract: We use near-infrared Integral Field Unit (IFU) data to analyze the galaxies NGC 4151 and NGC 1068, which have very different Eddington ratios - ˜50 times lower for NGC 4151. Together with a detailed data cube treatment methodology, we reveal remarkable similarities between both AGN, such as the detection of the walls of an "hourglass" structure for the low-velocity [Fe ii] emission with the high-velocity emission within this hourglass; a molecular outflow - detected for the first time in NGC 4151; and the fragmentation of an expanding molecular bubble into bullets of ionized gas. Such observations suggest that NGC 4151 could represent a less powerful and more compact version of the outflow seen in NGC 1068, suggesting a universal feedback mechanism acting in quite different AGN.